Self-Concept of Adolescents in Early Marriage and Divorce in Bruno District, Purworejo Regency - Rosa Lorinda; Nawari Ismail; Azam Syukur Rahmatullah (CV. Ridwan Publisher, 2023)
Divorce cases that occurred in Bruno District were ranked first in Purworejo Regency directly proportional to cases of early marriage. Data from the Office of Religious Affairs (KUA) of Bruno Sub-district, there were 15 cases of early marriage from 30 couples who got married in 2019. As a result of mental unpreparedness in building a household, it affects the way young couples solve a problem. This research is a qualitative research with a phenomenological approach. The phenomenon of young marriage by teenagers in Bruno Subdistrict, Purworejo Regency is influenced by several factors, namely economic factors, educational factors, parental factors, mass media and internet factors, biological factors, and pregnancy factors out of wedlock. Teenagers get married early because in Bruno District there are many cases of pregnancy outside marriage and promiscuity. Many young women and men who do early divorce are influenced by several factors, namely economic factors, maturity factors, communication factors, infidelity factors, heredity factors, educational factors, and environmental factors. The self-concept of the perpetrators of early marriage and early divorce in Bruno District, Purworejo Regency consists of a positive self-concept and a negative self-concept. Adolescents who have a positive self-concept are teenagers who try to be responsible according to their roles in the household both as husband and wife. Teenagers tend to have negative self-concepts about early marriage, where teenagers have the view that after marriage there is a physical change to become thinner.